Organize it! : how to declutter every nook and cranny in and outside your home - Kaufman, Mervyn (New York, 2006)
A room-by-room guide to organize the whole home once and for all. Includes inspirational photos, advice from top design pros and some favorite product ideas from Woman's Day magazine
Keywords: Interior decoration; Storage in the home